Questioning school failure as an individual problem: Reflections from a study of six schools in Callao (Revista Peruana de Investigación Educativa, 2016)
This paper discusses the phenomenon of school failure in the first grades of primary education, showing educational practices in six public schools in Callao, Peru. The research found that school failure is perceived as an individual problem by the school staff. Children and their families are blamed for the existence of learning difficulties and the educational system and practices that might cause them are not questioned. The strategy used by the schools to deal with this phenomenon was to make the students with learning difficulties repeat first grade, despite the existence of a national rule that set the compulsory and unrestricted promotion to second grade. However, this strategy reinforced the problem and usually led children and their families to resort to a psychologist. Additionally, it was also found that the number of children per classroom did not influence the attention to individual differences, since the educational system was organized to make all students advance at the same pace and rate. Considering these findings, the article ends by reflecting on how national policies and intervention measures face school failure.
Keywords: school failure; learning difficulties; learning process; attention to individual differences; social exclusion